The urgency of arabic in the study of the Qur'an - Ira Aniati; Irwan Saleh Dalimunthe; Nursri Hayati (At Turots: Jurnal Pendidikan Islam, 2023)
This study analyses the urgency of the Arabic language in the study of the Ulumul Qur'an. Arabic is essential for Muslims to study in order to fully comprehend the meaning of a verse in the Qur'an, especially for mufassir. As a result, the Arabic language and the Qur'an form a unified whole that cannot be separated. The writers applied a qualitative method patterned literature studies with descriptive analytic techniques in this research. The finding of this research is the study of Ulumul Qur’an which requires a comprehension od Arabic (ashwat, mufradat, qawa’id, and dilalah) where it can be seen in discussion of munasabah Al-Qur’an, muhkam and mutasyabih, the sound of ‘am and khash i’jaz, qasam, amtsal and Al-Qur’an interpretation (Tafsir).